2018
DOI: 10.9734/jamps/2018/44526
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Potential Drug Interactions in Hospitalized Cardiovascular Patients Using Three Knowledge Bases

Abstract: Background: Drug interactions continue to be an important cause of adverse effects, especially with cardiovascular drugs. Objective: This cross-sectional observational study aimed to recognize the frequency of potential drug-drug interactions (pDDIs) using three electronic knowledge bases (KBs); Lexicomp ® , Micromedex ® , and the free Drugs.com®, compare the inclusion and gradings of pDDIs in these three KBs and to identify associated risk factors. Methods: Medication orders of 125 patients in the cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 29 publications
4
3
0
Order By: Relevance
“…Authors of the Serbian study revealed a positive association between having an infectious or respiratory diseases and the presence of pDDIs [ 14 ]. Age did not have an effect on the presence of pDDIs as reported in three previous studies [ 7 , 16 , 17 ], which was consistent with our findings. The same factor did have an effect per three other studies [ 12 , 13 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Authors of the Serbian study revealed a positive association between having an infectious or respiratory diseases and the presence of pDDIs [ 14 ]. Age did not have an effect on the presence of pDDIs as reported in three previous studies [ 7 , 16 , 17 ], which was consistent with our findings. The same factor did have an effect per three other studies [ 12 , 13 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…When it comes to the influence of comorbidities on the pDDI prevalence, the results were conflicting. Similar to our findings, the number of comorbidities did not affect the prevalence of pDDIs as reported in two previous studies [ 7 , 16 ]. Three other studies found that the presence of comorbidities was a significant predictor for the prevalence of pDDIs [ 11 , 14 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations